Utilizing Islamic Ethics to Alleviate Multidimensional Problems In Nigeria - Abdulgafar, Olawale Fahm; Abdulraheem, Isiaka Olalekan; Ali Miqdad (AL-IKHSAN: Interdisciplinary Journal of Islamic Studies, 2024)
Nigeria faces numerous challenges stemming from immoral activities within its society, including corruption, terrorism, political dichotomy, economic instability, religious crises, and poor healthcare. Despite the government's efforts to combat these issues, the desired results have not been achieved. This study aims to investigate the potential of utilizing Islamic ethics, as outlined in the Qur'an and the sunnah of the Prophet, to address the multidimensional problems faced by Nigeria. By employing descriptive and qualitative research methods, relevant data was collected through questionnaire and analyzed. The findings highlight the failure of Nigeria to embrace Islamic ethical values as a significant factor contributing to the nation's problems. Specific instances illustrating the misalignment between prevailing ethics and societal challenges will be discussed.